Foreshock-induced slip transients set mainshock nucleation timing - Barnaby Fryer; Dmitry Garagash; Mathias Lebihain; François Passelègue (Nature, 2026)
Abstract Foreshocks are sometimes observed before earthquakes 1–13 , yet their role in controlling rupture nucleation remains unclear 1,11,14 . Classical models often assume that nucleation arises from slow, quasi-static slip governed primarily by fault weakening 15–21 , typically neglecting impulsive precursory events. Here we show, using laboratory experiments and a rate-and-state-based Griffith-like rupture framework 22 , that foreshocks, when they occur at the onset of or during nucleation, can fundamentally regulate earthquake initiation. We find that the slip burst induced by foreshocks imparts a transient sliding velocity, V min , whose magnitude is set by foreshock size and which robustly predicts both nucleation duration and spatial length. Larger foreshocks generate higher V min and trigger a more rapid transition to dynamic rupture, whereas smaller foreshocks produce long-duration quasi-static growth and very small impulses lead to ruptures entirely arresting. Extending our theoretical framework to tectonic faults, we show that foreshock and associated slow-slip sequences preceding natural earthquakes seem to follow the same scaling. These observations allow us to constrain realistic characteristic nucleation slip distances of 0.3–3.0 mm, orders of magnitude smaller than those inferred for dynamic rupture 23 . Our results demonstrate that foreshock-induced transients set the timing and potential detectability of earthquake nucleation 24 .